Types of biogenic quartz and its coupling storage mechanism in organic-rich shales: A case study of the Upper Ordovician Wufeng Formation to Lower Silurian Longmaxi Formation in the Sichuan Basin, SW China - Quanzhong GUAN; Dazhong DONG; Hualing ZHANG; Shasha SUN; Surong ZHANG; Wen GUO (Petroleum Exploration and Development, 2021)
Biogenic quartz in the Upper Ordovician Wufeng Formation to Lower Silurian Longmaxi Formation (Wufeng– Longmaxi) shale layers in the Sichuan Basin and its periphery is qualitatively analyzed and quantitatively characterized by organic petrologic, mineralogic, and geochemical methods to find out the coupling effect between organic matter and quartz. (1) There are two types of biogenic quartz in the shale layers: Type I quartz is submicron quartz appearing in clusters around the organic matter. Type II quartz is in nano-scale grain size and floats in spherical shape on organic matter, with grains in point-to-point or surface-to-surface contact; this type of quartz is mainly biologic origin and slightly affected by hydrothermal activity in local parts. (2) The reservoirs in the Wufeng–Longmaxi formations is consistent in distribution with biogenic silica content in them, and mainly concentrated at the bottom of the Wufeng–Longmaxi formations, and is thinner in the Changning and Weiyuan regions, while thicker in the Fuling region. (3) The biogenic quartz in the Wufeng–Longmaxi shale worked through the entire evolution process of hydrocarbon generation. The presence of biogenic quartz can enhance the development of organic matter pores and microcracks, and can effectively preserve the organic matter pores and residual intergranular pores, forming “biological silicon intergranular pores, organic pores and micro-fractures”. This would benefit later hydraulic fracturing and result in high production/stable production of well. The coupling effect between biogenic quartz development and organic matter evolution and hydrocarbon generation is a critical factor for high-quality shale reservoir development.